ANALISA HUMAN ERROR PROBABILITY MENGGUNAKAN METODE HEART (HUMAN ERROR ASSESSMENT AND REDUCTION TECHNIQUE) PADA OPERATOR KONVEKSI CV. 913 PRODUCTION - Prawira Ridzki Utama (Universitas Mercu Buana, 2018)
CV. 913 Production is convection in the Bekasi, West Java. This convection is producing jacket for men. The process of production in this convection, almost entirely made manually. Based on problems that often occurs in production process it caused by factors human error. Hence the CV.913 Production must have a high level of reliability. To deal with the problems of human error, a method that can be used is method of HEART (Human Assessment of Human Error). HEART method is the one of reduction technique in counting the probability of human error. From the settlement problem in CV. 913 Production by using the HEART method. So can be concluded that production activities that have bigger probability value of human error there are the process of designing and cutting raw materials. On both the process obtained probability value is 0.0104. The solution can researcher suggestions are to reduce the value of the error by operator was to set standards an operation these clearly and make one pattern which are permanent not to constantly changing.